Factors affecting the uptake of HIV testing among men: a mixed-methods study in rural burkina faso - Allegri, Manuela De; Agier, Isabelle; Tiendrebeogo, Justin; Louis, Valerie Renée; Yé, Maurice; Mueller, Olaf; Sarker, Malabika (© 2015 PLoS ONE, 2016)
Includes bibliographical references (page 13-15).